2021
DOI: 10.3390/buildings11070292
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Buriti (Mauritia flexuosa) Foam for Thermal Insulation and Sound Absorption Applications in Buildings

Abstract: Exploring new construction materials with low environmental impact leads to innovation in buildings and also to the expansion of environmental sustainability in the construction industry. In this perspective, the thermal insulation and the sound absorption performances of Buriti (Mauritia flexuosa) foam were analyzed for potential application in buildings. This material is of plant origin, it is natural, renewable, abundant, and has a low environmental impact. In this research, characterizations were made by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Meanwhile, the sound absorption coefficients at 500 Hz with the corresponded thickness are also displayed in Figure 13B. As indicated in these two figures, the RGO/PVA porous ceramics have better NRC values under the same thickness than other sound absorption materials 14,16–20,22,60–73 . In addition, at the same thickness, the RGO/PVA porous ceramics possess an excellent sound absorption coefficient at 500 Hz, indicating this hybrid porous ceramics can be utilized in a low‐frequency range.…”
Section: Resultsmentioning
confidence: 76%
“…Meanwhile, the sound absorption coefficients at 500 Hz with the corresponded thickness are also displayed in Figure 13B. As indicated in these two figures, the RGO/PVA porous ceramics have better NRC values under the same thickness than other sound absorption materials 14,16–20,22,60–73 . In addition, at the same thickness, the RGO/PVA porous ceramics possess an excellent sound absorption coefficient at 500 Hz, indicating this hybrid porous ceramics can be utilized in a low‐frequency range.…”
Section: Resultsmentioning
confidence: 76%
“…These values of thermal stability are slightly lower than other insulation com with lignocellulosic fibers in their composition [49][50][51]. However, the results sugge these materials can be used as a building material, since the stability temperature 260 °C is enough for building applications at low and medium temperatures [52].…”
Section: Thermal Stabilitymentioning
confidence: 80%
“…Images (b), (c) and (d) show the porous structure of the wheat straw fiber inside. This porous structure helps to enhance the thermal insulation of wheat straw giving it good properties for insulation material applications [54], because, in general, ma terials with closed pores, such as can be seen in wheat straw, have a lower thermal con ductivity than those with large and open pores [52].…”
Section: Wheat Strawmentioning
confidence: 99%
“…The open pores and the outer surface of the material form a continuous channel. When sound is incident on the surface of the material, the sound energy is converted into heat energy, and the sound energy dissipation is realized [37,38]. In addition, some studies have shown that adding an appropriate amount of glass fiber into concrete can effectively reduce the micro-cracks in concrete materials and improve their crack resistance and toughness [39][40][41].…”
Section: Introductionmentioning
confidence: 99%